Aesop's fables - Zipes, Jack (Penguin Books London, 2012)
Presents a collection of tale that includes such as a wily fox outwitted by a quick-thinking cicada, a tortoise triumphing over a self-confident hare and a fable-teller author silencing those who mock him.